The Influence of Activism by Institutional Investors on R&D - David, Parthiban; Hitt, Michael A.; Gimeno, Javier (Academy of Management Journal, 2001)
Researchers have assumed that large ownership stakes held by institutional investors grant them power to influence R&D investments. We found that ownership alone was insufficient and that institutions resorted to activism to influence R&D investments. Institutional activism increased R&D inputs over both the short and long terms. The nature of the activism and the strategic context of the R&D investment moderated the relationship. Further, R&D inputs mediated the effect of activism on R&D outputs.